A case report of early application of veno-arterial extracorporeal membrane oxygenation in amniotic fluid embolism. Issue 46 (19th November 2021) - Ge, Chen; Liu, Junhang; Fu, You; Jia, Lijing; Bai, Yinxiang; Yang, Zhiwei; Du, Quansheng
Abstract: Rationale: Amniotic fluid embolism (AFE) is a rare obstetrical complication and is a leading cause of maternal death in developed countries. Despite the development of supportive therapeutic measures, the mortality rate remains high. Patient concerns: A 38-year-old nulliparous pregnant woman, who underwent in vitro fertilization-embryo transfer, was admitted for labor at 37 weeks' gestation. Approximately 30 minutes after delivery of the placenta, the puerpera developed postpartum hemorrhage with uterine atony. Soon after, the patient experienced hypotension, repeated cardiac arrest, refectory hypoxia, and disseminated intravascular coagulopathy. Diagnosis: AFE is diagnosed clinically. The pregnant woman in this case fulfilled the diagnostic criteria for AFE: acute hypotension, cardiac arrest, acute hypoxia, and coagulation disorders within approximately 30 minutes after delivery of the placenta. Interventions: The patient was intubated, connected to a ventilator, and was administered a high dose of vasoactive drugs to maintain blood pressure and underwent an emergency hysterectomy. Considering the risk for recurrent cardiac arrest and severe refractory hypoxia, venoarterial extracorporeal membrane oxygenation was initiated and discontinued as soon as cardiac function was restored based on serial bedside ultrasound assessment. Outcomes: The patient stabilized on day 7 in the intensive care unit and was transferred to the obstetrics ward and, 1 week later, was discharged with no complications. Two months later, follow-up revealed that the patient was in good condition. Lesson: Serial bedside ultrasound was crucial for assessing cardiac function and optimal weaning. Timely application of venoarterial extracorporeal membrane oxygenation and weaning was significant to avoid the occurrence of complications and improve long-term outcomes.